Sources for the History of the ‘Fifth Province”: the Archive of the Federation of Galician Associations of the Argentine Republic - Farías, Ruy (Madrygal. Revista de Estudios Gallegos, 2017)
During XIX and XX Centuries Argentina was the most important destination for the migrations originated in Galicia. For at least five decades of the past century its capital city –Buenos Aires– was the city with the larger number of Galicians in the world. They created an extensive web of institutions of which since 1921 the Federation of Galician Associations of the Argentine Republic was part of. Over time, this institution has generated a significant volume of documentation that together with the archives of several micro-territorial Galician organizations and the extinct Republican Spanish Center of Buenos Aires make up for an impressive documental collection. In this paper I analyze the composition and characteristics of the Federations’ archive and I assess its value and the potential it has for the research of the Galician migration and exile in Argentina.